Os jornais paranaenses e a (in)visibilidade do negro e da sua educação (1853-1889) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This thesis presents a study on the education of black people portrayed on the Paraná’s newspapers from 1853 to 1889, the influences of the precepts of economic liberalism of John Locke on political, economic and educational positions in Brazil and in a singular way in Paraná. The choice for this period of analysis is justified by the important political events that took place, such as the Political emancipation of Paraná in 1853 and the search for clues about the black people and the education that circulated on newspapers at this time. Another important point to be highlighted was the important abolitionist laws that took place, such as: the Law of the Free Womb in 1871, the Law of Sexagenarians in 1885 and, in 1888, the Golden Law; yet the first steps of education in republican Brazil in 1889. The discussions held in the History, Society and Education Group of Campos Gerais in Paraná HISTEDBR-Campos Gerais also collaborated in the choice of this study. The adopted methodology was the historical materialism that has as reference the precepts of the Marxist theory. In this sense, we list as category for analysis of the object of study: contradiction, ideology, class struggle and totality; because we understand that the comprehension of the facts does not occur in an isolated or dissociated way of the real and material conditions that surround it. For the selection of primary sources, we start with the cataloging made by historian Marcia Elisa de Campos Graf, from newspapers in the oldest cities of Paraná in the period analyzed (1853-1889), such as: Paranaguá, Lapa, Castro, Curitiba, Campo Largo, Antonina and Morretes. The location of the journals under searching conditions was found in different archives, such as the Rare Works Session of the National Library, the National Digital Library, the Osvaldo Pilotto Collection, the Historical and Geographical Institute of Paranaguá, and the Neo-Pythagorean Institute . For a better understanding of the subject, the thesis was structured in three chapters. In the first chapter, we analyze the political and economic aspects portrayed in the Brazilian and Paraná press under the aegis of liberalism. In the second chapter, we discuss the conditions of the black man and slave and free labor in Brazil and, particularly in Paraná, recorded by the press. In the third chapter, we analyze the impressions present in the newspapers of Paraná, about the education for the black of a prejudiced, discriminatory and segregationist nature, permeated by the liberal precepts. In the final considerations, we weave the impressions that were being constructed in the study, and defend the thesis that pointed to the (in) visibility of the black people on newspapers from Paraná in relation to his work and education.
Keywords: Educação do Negro; Imprensa; Liberalismo; Paraná; HISTEDBR- Campos Gerais; Black people Education; Press; Liberalism; Paraná; HISTEDBR-Campos Gerais; CNPQ::CIENCIAS HUMANAS::EDUCACAO